(untitled) (International Journal of Engineering and Computer Science, 2018)
The need to have rapid access to various service by various customers brought about the introduction of cloud e-marketplaces. The goal of the cloud e-marketplace is to attract the biggest possible number of buyers and also ensure that the quality of the delivered services is sustained. Even though various literatures exist on cloud oriented marketplace, most of these literatures are short of some important details. This review paper provides a better literature on cloud oriented e-marketplaces by discussing the evolution, features, existing research, challenges and in addition, concluded that the future approach that will allow optimized performance in cloud e-marketplaces’ would be to consider the servers being used for cloud service delivery as a group of distributed systems.